The gut microbiome as a factor in the development of Parkinson's disease - L. A. Brsikyan; E. A. Poluektova; M. G. Poluektov (Неврология, нейропсихиатрия, психосоматика, 2023)
Parkinson's disease (PD) is a neurodegenerative disease characterized by the progressive death of dopaminergic neurons in the substantia nigra of the brain and the deposition of α-synuclein in the form of Lewy bodies in other parts of the brain. Characteristic manifestations of this disease, along with motor symptoms, are the gastrointestinal tract disorders, accompanied by a change in the cellular composition of the intestinal biocenosis. This made it possible to propose the so-called "intestinal" theory of the PD origin. According to this theory, degenerative changes begin in the nervous apparatus of the large intestine, and then spread to the brain. Changes in the intestinal microbiota composition can contribute to the development of the neurodegenerative process through neural, immune, endocrine mechanisms, as well as through biologically active substances.